On the Existence of an Optimal Income Tax Schedule - Kaneko, Mamoru (Review of Economic Studies, 1981)
Journal Article On the Existence of an Optimal Income Tax Schedule Get access Mamoru Kaneko Mamoru Kaneko University of Tsukuba and Yale University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 48, Issue 4, October 1981, Pages 633–642, https://doi.org/10.2307/2297202 Published: 01 October 1981 Article history Received: 01 June 1980 Accepted: 01 April 1981 Published: 01 October 1981